Diagrammatic representation of the nexus between agrobiodiversity, climate change, nutrition and health outcomes - Ekesa, Beatrice (2023)
The diagraph shows the relationship between agrobiodiversity, climate change, dietary practices and implications on nutrition outcomes and health (physical and mental) outcomes.